The crystal structure of 5,7-dinitropyrazolo[5,1-b]quinazolin-9(4H)-one, C10H5N5O5 - Jin Shouwen; Zhang Qiong; Zhen Yaoqi; Shi Chengzhe; Wang Daqi (Zeitschrift für Kristallographie - New Crystal Structures)
C10H5N5O5, monoclinic, P21/c (no. 14), a = 10.9546(11) Å, b = 7.3433(8) Å, c = 13.2567(15) Å, β = 102.972(5)∘ $102.972{(5)}^{° }$ , V = 1039.19(19) Å3, Z = 4, Rgt ${R}_{gt}$ (F) = 0.0630, wRref $wR_{ref}$ (F 2) = 0.1622, T = 298 K.